Mining from the Lens of Ecological Law: Obstacles and Opportunities for Re-formation - Sbert Carlsson, Carla (Université d'Ottawa / University of Ottawa, 2019)
Ecological law is a legal paradigm that is emerging in response to the current ecological crisis. This thesis explores the main challenges and opportunities in existing laws, particularly in the context of mining, for a shift to this new paradigm. A synthesis of the main critiques, scientific and economic concepts, legal scholarship and proposals that contribute to the theory of ecological law is presented, along with a discussion of the relationship and potential synergies of ecological law with Indigenous legal traditions and with Green Legal Theory. An analytical tool to help improve the understanding of what a shift to ecological law would entail–a lens of ecological law–is proposed, building on ecological law scholarship. The lens of ecological law consists of three principles of ecological law: ecocentrism, ecological primacy and ecological justice. This lens is applied to three different legal approaches to mining in order to reflect on the implications for a shift to ecological law in this sector: El Salvador’s ban on metal mining; mineral extraction proposed in Ontario’s Ring of Fire; and mining in the context of the rights of Mother Earth and vivir bien recognized in Bolivian law. Conclusions on the obstacles and opportunities for a shift to ecological law in mining, and recommendations on the ecological law re-formation of mining and on further research are offered in closing. Ecological law promises to be an important part of building an ecologically just society.
Keywords: ecological law; mining; environmental law; sustainability law; degrowth; rights of nature; El Salvador mining ban; Ring of Fire mining; Bolivia Rights of Mother Earth